Implementing Weights for Additivity of Chained Volume Measures in the National Accounts - Jesus C. Dumagan (Philippine Institute for Development Studies (PIDS), 2011)
In current practice, subaggregate chained volume measures (CVMs) are neither weighted nor additive. This paper derives and implements "weights" for weighted subaggregate CVMs to be additive (i.e., their sum equals aggregate CVM) because without weights, nonadditivity permits the nonsensical result that a subaggregate CVM could exceed aggregate CVM. The weights are ratios of subaggregate to aggregate chained price deflators that exceed, equal, or fall below 1 depending on relative prices. CVMs in current practice are additive in the special case of constant relative prices when all weights equal 1. If relative prices change, weights do not equal 1 and their use avoids nonadditivity and the above nonsensical result. Empirically, they have widespread implications because CVM is now implemented in over 40 countries. Application to actual GDP data shows significant distortions of GDP composition due to nonadditivity of subaggregate CVMs from ignoring relative price changes. Among this paper's formulas for additive weighted subaggregate CVMs, the one based on Paasche price and Laspeyres quantity indexes is recommended for practical implementation.
Keywords: C43; 330; additivity; chained volume measure; Government Service Insurance System (GSIS); Social Security System (SSS); GDP in chained prices; chained index; Nationaleinkommen; Volkswirtschaftliche Gesamtrechnung; Philippinen